A neutralizing monoclonal antibody targeting the acid-sensitive region in chikungunya virus E2 protects from disease. - Suganya Selvarajah; Nicole R Sexton; Kristen M Kahle; Rachel H Fong; Kimberly-Anne Mattia; Joy Gardner; Kai Lu; Nathan M Liss; Beatriz Salvador; David F Tucker; Trevor Barnes; Manu Mabila; et al. (Public Library of Science (PLoS), 2013)
The mosquito-borne alphavirus, chikungunya virus (CHIKV), has recently reemerged, producing the largest epidemic ever recorded for this virus, with up to 6.5 million cases of acute and chronic rheumatic disease. There are currently no licensed vaccines for CHIKV and current anti-inflammatory drug treatment is often inadequate. Here we describe the isolation and characterization of two human monoclonal antibodies, C9 and E8, from CHIKV infected and recovered individuals. C9 was determined to be a potent virus neutralizing antibody and a biosensor antibody binding study demonstrated it recognized residues on intact CHIKV VLPs. Shotgun mutagenesis alanine scanning of 98 percent of the residues in the E1 and E2 glycoproteins of CHIKV envelope showed that the epitope bound by C9 included amino-acid 162 in the acid-sensitive region (ASR) of the CHIKV E2 glycoprotein. The ASR is critical for the rearrangement of CHIKV E2 during fusion and viral entry into host cells, and we predict that C9 prevents these events from occurring. When used prophylactically in a CHIKV mouse model, C9 completely protected against CHIKV viremia and arthritis. We also observed that when administered therapeutically at 8 or 18 hours post-CHIKV challenge, C9 gave 100% protection in a pathogenic mouse model. Given that targeting this novel neutralizing epitope in E2 can potently protect both in vitro and in vivo, it is likely to be an important region both for future antibody and vaccine-based interventions against CHIKV.